Accelerated high-quality dual-wavelength digital holography using direct-retrieved synthetic-phases. (June 2023) - Shan, Mingguang; Meng, Na; Yu, Lei; Zhong, Zhi; Xie, Yongqiang; Liu, Bin; Liu, Lei
Highlights: Differing from the present approaches utilizing the intermediate wrapped phases at each wavelength to obtain the synthetic-phases, the proposed method reconstructs the synthetic-phases directly, and then alleviate boundary conditions during the unwrapping process. It can offer speed with simplicity according to both computational process and burden. Both the numerical and experimental results illustrate that the proposed method can perform QPI with high accuracy and fast speed for off-axis dwDH. Abstract: Linear programming algorithm (LPA) using synthetic-phases can provide high quality quantitative phase imaging for dual-wavelength digital holography (dwDH). However, they are time-consuming owing to the complex process and heavy burden in computation. In this paper, an efficient LPA is developed to perform fast and accurate imaging for dwDH, in which both the additive and differential synthetic-phases are reconstructed in straightforward ways. After reconstructing the two synthetic-phases using multiplication-division and division-division multiplexing, respectively, the proposed method searches the optimal integer in one dimensional boundary condition to match the two synthetic-phases, and then yields the measured height map with high accuracy as well as fast speed. We demonstrate both the numerical and experimental results to evaluate the feasibility and effectiveness of the proposed method.